2016
DOI: 10.1080/17445302.2016.1194555
|View full text |Cite
|
Sign up to set email alerts
|

Wetdeck slamming loads on a developed catamaran hullform – experimental investigation

Abstract: Catamaran wetdeck slamming has been experimentally investigated using a servo hydraulic slam testing system. A series of controlled-speed water impacts was undertaken on a rigid catamaran bow section with two interchangeable centrebows. Entry into the body of water was at two fixed trim angles; 0 and 5 degrees. The vertical velocity was varied from 3 to 5 m/s in 0.5 m/s increments. This study presents a new dataset of pressure distributions and slam forces on the arched wetdeck structure of catamaran vessels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The present work extends upon the experimental works conducted by Swidan et al(2016) and Swidan et al (2017) through providing non-dimensionalised pressure coefficients of the maximum pressure peaks of a catamaran during water-entry at two relative impact angles and range of impact velocities. It is very useful to represent pressure in terms of a dimensionless quantity, like that of lift and drag, as a step forward to eliminate the uncertainty related to experiments with scaled models, which is an issue currently being discussed by the international scientific community (Rizzo et al, 2018).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The present work extends upon the experimental works conducted by Swidan et al(2016) and Swidan et al (2017) through providing non-dimensionalised pressure coefficients of the maximum pressure peaks of a catamaran during water-entry at two relative impact angles and range of impact velocities. It is very useful to represent pressure in terms of a dimensionless quantity, like that of lift and drag, as a step forward to eliminate the uncertainty related to experiments with scaled models, which is an issue currently being discussed by the international scientific community (Rizzo et al, 2018).…”
Section: Introductionmentioning
confidence: 77%
“…However, there are limited data available in the public domain, which is just limited to 2-d multihull vessels (Davis and Whelan, 2007, Swidan et al, 2014, Swidan et al, 2013). An exception is the study conducted by Swidan et al( 2016) and Swidan et al (2017), where two series of 3-d drop tests were performed to evaluate the behaviour of a catamaran bow section during the water-impact phase at a range of constant speeds from 2.5m/s up to 5m/s in 0.5m/s increments.…”
Section: Introductionmentioning
confidence: 99%
“…However, the peak pressures are relatively higher for the Long CB (especially from Fr 66 to 73), and lower for the Short CB (especially for the inboard positions), than the Parent CB. It is worth noting that the drop tests of Swidan et al [11,12] showed that the impact pressures at various longitudinal positions is proportional to squared impact velocity, and is strongly location dependent. They also found that the magnitude of peak pressure decreased from the bow truncation (located between Fr 70 and Fr72) to the bow.…”
Section: Centre Bow Slamming Loadsmentioning
confidence: 99%
“…For general ship slamming many are reviewed by Kapsenberg [8] and Hirdaris et al [9]. In WPCs experimental techniques have been used extensively for the identification of slam loads, including drop tests [10][11][12], scale model tests [13][14][15][16][17] and full scale trials [18,19], along with several numerical investigations, for example [20,21]. Davis and Whelan [10] systematically studied CB geometry in drop tests, recommending modifications to bow flare angle and archway clearance of Incat catamarans to reduce the slamming pressures over the impact area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation